2007
DOI: 10.1103/physrevlett.98.193401
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Internal Energy of FragmentedC60

Abstract: A new experimental approach has been investigated to measure directly the internal energy of fragmented C60. Doubly charged C60{2+*} prepared in collisions H++C60-->H- +C60{2+*} decay by evaporation of C2 units. We have measured the internal energy distribution of the transient C60{2+*} for each decay channel by analyzing the kinetic energy loss of the scattered anion H-. This method offers an experimental opportunity for studying the fragmentation dynamics of more complex systems such as larger clusters and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Pioneering experimental work reported in Refs. [13,14] has already been performed in order to determine the actual energy-deposit distributions in ionmolecule collisions, as well as to study its relationship with the observed fragmentation patterns. However, these methods require the knowledge of the initial and final projectile states which is only straightforward in the case of doubleelectron capture by singly charged ions (e.g., H þ → H − ), which is more the exception than the rule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering experimental work reported in Refs. [13,14] has already been performed in order to determine the actual energy-deposit distributions in ionmolecule collisions, as well as to study its relationship with the observed fragmentation patterns. However, these methods require the knowledge of the initial and final projectile states which is only straightforward in the case of doubleelectron capture by singly charged ions (e.g., H þ → H − ), which is more the exception than the rule.…”
mentioning
confidence: 99%
“…Thus, the knowledge of the distribution of the energy transferred to the molecule plays a key role to unravel its fragmentation dynamics. It is difficult to assess experimentally this energy distribution even if translational spectroscopy can provide it in the case of multiple electron capture [13,14].…”
mentioning
confidence: 99%
“…5 we show median values for the total energy loss per C 60 molecule in the cluster as a function cluster size. The deposited energy is shared between the individual molecules such that they become cold enough to stay intact and to be detected as C be in the range of about 50 eV or below as has been measured directly by Martin et al 27 and this is indeed the case for the median energy per molecule for clusters larger than about n = 10 for 13 keV Ar 2 + + [C 60 ] n collisions. For He 2 + collisions at 22.5 keV much less energy is transferred for a given cluster size and this readily explains why the emitted C + 60 ions are colder and more often stay intact for He 2 + -than for Ar 2 + -collisions (cf.…”
Section: A Monte Carlo Calculation Of Stopping Energiesmentioning
confidence: 53%
“…C 2 emission from C q+ 60 is found to dominate when q 2 while C + 2 emission dominates when q 5, in agreement with the present and previous experimental results. DOI Over the past decades, fullerenes have been extensively studied by means of various excitation and ionization agents, such as photons [1][2][3], electrons [4][5][6][7][8], ions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], or laser pulses [25][26][27][28][29][30]. It has been demonstrated that hot fullerene ions produced in these interactions may cool down by electron emission [29,[31][32][33], radiative decay [34,35], or by statistical fragmentation processes [36][37][38][39].…”
mentioning
confidence: 99%